Aerial Photographs of Barter Island, Bethel RRS, Bullen Point SRRS, Campion, Cold Bay LRRS, Oliktok LRRS, Point Barrow LRRS, Point Lay LRRS, Point Lonely SRRS, Wainwright SRRS - 611th Civil Engineer Squadron (611th Air Support Group, United States Air Force, 2021)
Aerial photographs of various radar sites from Alaska's Radar System.